(untitled) (Praxis Educativa, 2026)
In this article we present and discuss results from an educational research project that examines the forms taken by processes of knowledge production, circulation, transmission, and acquisition in postmedia society. We begin from the hypothesis that the classroom can be understood as a socio-technical assemblage in which the intersection of school knowledge, everyday experiences, and digital artefacts does not constitute a secondary effect, but rather a condition of possibility for the production of knowledge. To explore this problem, we analyse a transdisciplinary pedagogical project developed during 2025 in a public secondary school in the Metropolitan Region of Buenos Aires, in collaboration with the university. Drawing on contributions from new materialism, posthumanism, and postmedia studies, we approach the classroom as a heterogeneous web in which multiple human and non-human agencies become intertwined and co-constituted, examining what connections emerge and what experiences of knowledge are enabled through these relations.